PENERAPAN TEORI ANTRIAN PADA PELAYANAN TELLER BANK X KANTOR CABANG PEMBANTU PURI SENTRA NIAGA - Nia Puspita Sari; Sugito Sugito; Budi Warsito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2017)
Bank X Puri Sentra Niaga branch office is one of bank that can not be separated from the queue issue. The customers want a fast and easy service. The length of queueing and the long waiting times may cause customers cancel the transaction and choose another bank. Therefore, it is necessary to define a suitable queueing model of teller service. Bank X Puri Sentra Niaga branch office have two types of teller service namely Antrian 1 and Antrian 2. Queueing model for Antrian 1 is (M/G/1):(GD//). The model describe that the customers arrival distribution is Poisson, the customer service distribution is General, the number of server is 1, the service disipline is FIFO (first in first out), the customers capacity and the resource of customers are infinite. Queueing model for Antrian 2 is (M/M/2):(GD//). The model describe that customers arival distribution and service distribution are Poisson, the number of server is 2, the service disipline is FIFO (first in first out), the customers capacity and the resource of customers are infinite. Software Arena is applied in simulation to compare the measures of performance if the number of teller added.Keywords: Queue, Queueing System Model, Bank, Teller.